Fisheries Management and Habitat Conservation at Kutaraja Ocean Fishing Port - Mardhatillah, Inda; Fajri, Ilham; Fuah, Ricky Winrison; Nurhayati; Pandang, Ivonda Vicana; Dolorosa, Maretty Twentyna (Journal of Fish Health, 2025)
The Kutaraja Ocean Fishing Port (PPS Kutaraja) is one of the largest fish landing sites in Banda Aceh, playing a significant role in shark fisheries, particularly for thresher sharks (Alopias pelagicus). This study aims to describe the thresher shark fishery at PPS Kutaraja, assess the status of its utilization, and provide recommendations for sustainable management. The research was conducted through direct observations, interviews with fishermen and fishery business operators, and secondary data analysis. The results indicate that thresher sharks are primarily caught as bycatch using purse seines and longlines. The shark trade at PPS Kutaraja involves multiple stakeholders, from fishermen and intermediaries (toke bangku) to domestic and international markets. Habitat and ecosystem assessments reveal that seagrass and coral reef ecosystems along the Aceh coast are in moderate condition, while mangrove ecosystems remain relatively well-preserved. The composite evaluation of the Ecosystem Approach to Fisheries Management (EAFM) for habitat and ecosystem aspects scored 66.67, categorized as "good." However, the lack of data on key shark habitats, such as spawning, nursery, and feeding grounds, highlights the need for further research. To ensure sustainability, ecosystem-based management strategies, including establishing conservation areas and stricter monitoring of shark fishing practices, are recommended. Implementing effective policies will support the long-term sustainability of thresher shark fisheries at PPS Kutaraja.